Combined acoustic-mechanical analysis during storage of scallion (Allium fistulosum) minimally processed (Scientia Agropecuaria, 2012)
Scallion (Allium fistulosum) is a highly perishable green vegetable due to its moisture content, its high metabolic rate and their poor conditions of post-harvest during to harvest and transport. The objective of this research was to determine the relationship between visual deterioration´s product and changes generated in the mechanical and acoustic properties of the same. The scallion grown in Aquitania, Boyacá Colombia was stored under different conditions of storing: vacuum packed (10 mbar) and unpacked (HR 68%) and storage temperature 4 ºC and 16 ºC until deterioration by visual appearance. The acoustic mechanical changes in firmness, crispness and fracture for unpacked scallion and stored at 4 °C occurred on day 15 of storage, and visual deterioration on day 13. For the unpacked product and stored at 16 °C, the biggest change was presented at sixth day. The vacuum packed product, stored at 4 °C presented mechanical, acoustic and visual appearances changes at 15 day and for the product packaged under vacuum and stored at 16 ° C showed changes on day six in the characteristics of firmness, crispness and fracturability, coinciding with the decrease in visual appearance. In general terms the change was more noticeable decrease in fracturability for scallion stored at 16 °C, in the two packaging conditions. Instrumental methods used to approximate the deterioration´s time of minimally processed scallion were adequate to establish shelf life perceived by visual appearance.
Keywords: scallion; texture; crispness; storage.